Efektivitas Teknik Konseling Feminis dalam Menangani Kasus Diskriminasi Gender di Kalangan Remaja - Putri Amalia; Nayla Azka Bilgina; Rahma Nurul Wahidah; Eka Fitriani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Gender discrimination is a serious problem that is often experienced by adolescents in social and educational environments. Feminist counseling techniques are present as an alternative approach that emphasizes equality, empowerment, and validation of client experiences, especially women. This study aims to determine the effectiveness of applying feminist counseling techniques in helping adolescents face and overcome the impact of gender discrimination. The method used is a descriptive qualitative study with a case study approach on several adolescents and school counselors. The results showed that techniques such as self-disclosure, reframing, and self-empowerment were effective in increasing adolescents' self-confidence, critical awareness, and courage in voicing gender injustice. The main obstacles in implementing these techniques are the counselors' lack of understanding of feminist principles and limited counseling time in schools. Therefore, training and institutional support are needed to optimize this approach.